Oral Health Knowledge and Practice of Caregivers of Institutionalized Elders - Gomes, Patricia da Costa; Valentim, Flavia Bridi; Martinelli, Katrini Guidolini; Rosetti, Elizabeth Pimentel (ARCHIVES OF HEALTH INVESTIGATION, 2021)
Background: Caregivers play an important role in maintaining adequate oral health of elders. Objective: The aim of this study was to evaluate the oral health knowledge and practice of caregivers of institutionalized elders in Brazil. Methods: This was a cross-sectional study with a sample of 27 caregivers from a long-term care institution in the city of Vitória, State of Espírito Santo, Brazil, between July and October, 2016. A form was used to assess the following characteristics of caregivers: profile, training, knowledge, practice and prevention related to oral health. All data were analyzed by descriptive statistics. Results: The predominant profile of the caregivers was: female (63%) and 81.5% were trained to work with elders. Although most of them knew the necessity of tooth brushing at least three times a day to prevent dental caries and periodontal disease (88.9%); 44.5% said that the caregivers performed oral hygiene for the elderly under supervision only once a day. Regarding the hygiene of dentures, only one caregiver mentioned the use of a specific chemical agent; 40.7% declared themselves unaware of any oral care protocol at the institution; 85% believed in a correlation between general health and the presence of oral diseases; 70% declared they did not know about oral diseases that could affect elders with dentures in function, and 59.3% answered that the type of food may influence oral health. Conclusions: Caregivers acknowledged and recognized the importance of oral health, but their practice was not consistent with their declared knowledge.